Integrasi Model Pembelajaran Project Based Learning (PJBL) Terhadap Kemampuan Literasi Matematika Pada Siswa Sekolah Dasar - Nurhayati Nurhayati; Esra Retorika Simanullang; Fitri Handina Dongoran; Syahrial Syahrial (CV. Aksara Global, 2024)
Mathematics is a fundamental science that underpins many aspects of daily life. Where mathematics can be used as a method of solving problems that we face in life activities, such as in using information, knowledge and seeing and using relationships between objects. Not only that, the important role of mathematics includes the formation and development of rational, logical, systematic and critical thinking skills. In the study conducted by Putrihapsari and Fauziah (2020), Nazir (2014) defines literature study as a research approach that involves evaluating a multitude of literature studies that are pertinent to the research being conducted. This strategy is employed in research as a preliminary stage to organise the investigation by gathering data from literature in the subject, without the necessity for direct involvement. By using the PjBL model, it is hoped that it can cover 21st century skills so that it can improve the quality of students' mathematical literacy skills. Given that students must collaborate from the outset, the Project Based Learning (PjBL) learning paradigm may assist them in developing the skills required to work effectively in groups. In order for students to comprehend the rationale and benefits of the mathematics education they receive in the classroom, this learning paradigm is essential for fostering mathematical literacy.